EFFORT, SUCCESS, AND CHARACTERISTICS OF SPRING TURKEY HUNTERS ON TALLAHALA WILDLIFE MANAGEMENT AREA, MISSISSIPPI - William E. Palmer; George A. Hurst; John R. Lint (Wildlife Society Bulletin)
Abstract: The increasing number of wild turkey (Meleagris gallopavo) hunters in Mississippi necessitates an understanding of the effect of hunter effort on harvest and hunter success rates relative to turkey population size. Hunter effort and success were studied for 6 spring gobblers‐only hunting seasons on a public hunting area in Mississippi. An average of 32 gobblers was harvested and hunter effort averaged 502 hunter‐days per year. Hunter success rate averaged 6.5%. An average of 25.8% of the pre‐hunting season gobbler population was harvested. Hunter success rates were correlated with gobbler call counts (P = 0.03), but, only weakly correlated with population estimates (r = 0.57). Daily harvest and hunter effort were positively correlated (P = 0.000). Hunter success rates were inversely correlated with hunter effort (P = 0.03). There were more hunters on weekends (P = 0.000), and hunters on weekends had lower success rates (P = 0.007). Although 1 in 6 unique hunters harvested a turkey, fewer than 20% of hunters returned after their first year. Hunter effort did not decline in seasons with low gobbler populations or in years with low gobbling activity. The low return rate of hunters to Tallahala Wildlife Management Area and the inverse relationship between daily hunter effort and success per hunter may indicate that hunter density was too high for a quality hunting experience. Hunter density could be limited to increase hunter satisfaction.